Modeling Accuracy in FEA of Vibrations of a Drumhead - Robert J. Melosh (Shock and Vibration)
The study of the problem of predicting values of Rayleigh’s quotient for a square drumhead provides a basis for assessing the relation between grid size, accuracy of analysis results, and efficiency of data processing in finite element analysis. The analysis data indicate that unacceptable grid sampling can occur even for the fine grids, that strictly monotonic convergence is attainable for vibration analysis, and that more efficient computer analysis associates with use of curve fitting analysis of conventional finite element analysis results.